Sprint interval training improves aerobic and anaerobic power in trained female futsal players - Beyranvand, F. (International Journal of Kinesiology & Sports Science, 2017)
Background: Various sprint interval training (SIT) programs have been used with athletes from a wide range of sports to evaluate its effects on physiological and performance adaptations. However, information regarding the effect of a short period of SIT on physiological adaptations of trained female futsal players is limited. Objective: This study evaluated the influence of sport specific SIT on anaerobic power and aerobic power in trained female futsal players. Method: Several aspects of VO2max and Wingate-based power were measured after SIT program performed for 4 weeks. Following pre-test, 16 trained female futsal players (VO2max = 41.21 ± 3.35 ml.kg-1.min-1) were randomized to either an intense exercise training consisting of sets of 5×40 meter maximum sprint efforts interspersed by a 10-second rest between sprints (3,4,5,6 sets/session from 1st to 4th week respectively with 3 minutes of recovery between sets), performed two sessions a week over 4 weeks (n=8) or a usual training control group (n=8). Results: Significant (except as shown) improvements (p < 0.05) after SIT were seen in: VO2max (5.8%), vVO2max (6%), VO2/HR (6.5%), peak power output (PPO) (7.6%), and mean power output (MPO) (14.9%), but no significant change was found in Heart rate at V?O2max. Also, no significant enhancement in mentioned variables was found in the CON group. Conclusion: Present results indicate 4 weeks of sprint interval training program with low volume is associated with improvements in VO2max, vV?O2max, VO2/HR, PPO, and MPO in trained female futsal players.